‘The coldest case of all’: Fire investigation at the Viking Age ring fortress of Borgring, Denmark - Ljungkvist, Eva; Thomsen, Benny; Sindbæk, Søren Michael; Christensen, Jonas; Holm, Nanna; Schultz, Maja Kildetoft; Ulriksen, Jens (Danish Journal of Archaeology, 2022)
During excavations of the Viking-age ring fortress Borgring, Denmark, traces of a devastating fire was uncovered. The National Forensic Services of the Danish Police were invited to participate in a novel collaboration, applying contemporary forensic fire investigation to an archaeological site. This paper presents the results and sets a benchmark for future applications. The investigation leads to a revised reconstruction of the fortress and the development of the fire. The application of fire investigation methods, following the Daubert standard criteria, enhance the documentation and analysis of archaeological sites, while archaeological methods show significant potential at modern fire scenes.